Philosophy and theology: Reviews from Stellenbosch - Proposals from Paris? - Ullrich, Calvin Dieter (Stellenbosch Theological Journal, 2022)
The contributions of "the turn to religion" in continental philosophy have begun to find their place in South African theological and philosophical circles. This article asks: how are we to position this phenomenon in the South African context and what implications it might have for the future of systematic theology? After situating the "turn to religion" in general, the article traces the historical development of philosophy's creative relationship to theology by focusing on three representatives from the Stellenbosch tradition: the theologian Johannes du Plessis, the philosopher J.F. Kirsten, as well as the philosopher, Johann Degenaar. It argues that the relationship between philosophy and theology cultivated in these figures is characterized by what can be called the "propaedeutic" model, whereby theology is subjected to a "preparation" by philosophy. This model raises questions about the "use" of philosophy in contemporary systematic theology within the context of the secular academy and an ever-pluralizing world. The article suggests that recent debates in the continental "turn" are uniquely positioned to help reflect on such questions of methodology, and to this end makes a tentative proposal drawing on the philosophical-theological approach developed by the French thinker, Emmanuel Falque.